2022
DOI: 10.3390/jcm11102728
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Regional Kidney Perfusion during Surgical Pneumo-Peritoneum Creation and the Risk of Acute Kidney Injury—A Review of Basic Physiology

Abstract: Acute kidney injury (AKI), especially if recurring, represents a risk factor for future chronic kidney disease. In intensive care units, increased intra-abdominal pressure is well-recognized as a significant contributor to AKI. However, the importance of transiently increased intra-abdominal pressures procedures is less commonly appreciated during laparoscopic surgery, the use of which has rapidly increased over the last few decades. Unlike the well-known autoregulation of the renal cortical circulation, medul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 164 publications
(268 reference statements)
0
9
0
Order By: Relevance
“…This may be due not only to the compression of the central venous system but also to that of renal parenchyma, with an impairment of renal venous drainage, lymphatic drainage or both. Although the threshold of IAP for kidney damage seems to be about 15 mmHg in humans [ 13 , 27 ], the presence of comorbidities, the increasing complexity of surgical interventions and prior episodes of post-operative acute kidney (PO-AKI) can make some patients susceptible to kidney damage, even at an IAP < 15 mmHg [ 27 ]. Therefore, any means of reducing IAP without hindering surgical conditions has the potential of reducing the risk of post-operative kidney injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due not only to the compression of the central venous system but also to that of renal parenchyma, with an impairment of renal venous drainage, lymphatic drainage or both. Although the threshold of IAP for kidney damage seems to be about 15 mmHg in humans [ 13 , 27 ], the presence of comorbidities, the increasing complexity of surgical interventions and prior episodes of post-operative acute kidney (PO-AKI) can make some patients susceptible to kidney damage, even at an IAP < 15 mmHg [ 27 ]. Therefore, any means of reducing IAP without hindering surgical conditions has the potential of reducing the risk of post-operative kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The PO-AKI stage 1 of KDIGO classification [ 13 ] is a moderate PO-AKI that is often reversible and therefore little considered in clinical practice and often not recognized post-operatively. Unfortunately, patients with some grade of PO-AKI show significantly inferior survival rates compared to patients with normal kidney function, and recurrent AKI represents a risk factor for the future decline of kidney function [ 27 ]. Therefore PO-AKI KDIGO 1 should not be underestimated and should be recognized early in order to increase the level of patient surveillance and avoid worsening to other more severe stages of PO-AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease risk varies regionally and is always complex. Several studies have reported that physiological variation may be a factor [ 62 , 63 ], including genetic factors and lifestyle factors, such as eating habits, smoking, alcohol, and physical activity [ 64 , 65 ], as well as environmental factors, such as pollution, socioeconomic status, and stress, and access to public health services [ 66 , 67 ]. However, the gradual improvement of AKI symptoms, early screening, and the identification of AKI risk factors can improve the situation.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Medullary hypoperfusion may result in multiple destructive events: i) tubular destruction; ii) tissue hypoxia (cytoskeletal disruption, loss of brushborder microvilli, devastated cell junctions, mislocation the sodium-potassium ATPase from the basal to the apical surface of epithelial cells, activation of harmful proteases, and phospholipases) and ischemia-reperfusion injury; iii) various types of programmed cell-death events; iv) obstruction of the tubular lumen by debris of destroyed cells; v) back-leak of filtrate to the circulation through damaged tubular wall; and vi) insoluble gel cast formation by polymerization of Tamm-Horsfall protein due to impaired sodium resorption and elevated intraluminal sodium concentration. [51][52][53] Second, the consequences of chronic hypertension with structural changes in renal arterioles and capillaries leading to compromised internal diameter and increased secretion of renin are identified as the susceptibility factors of kidneys to ischemic insults. 51,52 Third, pharmacologic agents may influence the glomerular filtration pressure.…”
Section: Hemodynamic and Oxygen Supplymentioning
confidence: 99%